Software technologies : applications and foundations : STAF 2016 Collocated workshops: DataMod, GCM, HOFM, MELO, SEMS, VeryComp, Vienna, Austria, July 4-8, 2016, revised selected papers /: applications and foundations : STAF 2016 Collocated workshops: DataMod, GCM, HOFM, MELO, SEMS, VeryComp, Vienna, Austria, July 4-8, 2016, revised selected papers. (2016) - Unknown
No abstract available